Implementation of the Aswaja Course in Shaping Moderate Islamic Character - Zainudin, Agus; Yanuardianto, Elga (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
The implementation of Aswaja courses at the Islamic University of Jember (UIJ) in forming students' Wasathiyah Islamic character (Islamic moderation) is the main subject of this study. The primary study issue is how UIJ's Aswaja course model helps students develop a moderate Islamic character and how well the university has done at doing so. This research will employ a case study with a qualitative approach and provides a detailed examination of a specific environment, object, or collection of documents or events. To achieve the research objectives, the researcher conducts field observations, structured or unstructured interviews with key personnel at the Islamic University of Jember, and document analysis to supplement data. Data collection will occur in a natural setting, with the researcher observing without prior arrangement, aiming for their presence to maximize the study's objectives effectively. The integration of Ahlussunnah wal Jamaah values in education at the Islamic University of Jember (UIJ), who revealed various strategies and policies the university employs to internalize Aswaja values in every aspect of education, it was found that Aswaja values such as moderation (tawasuth), balance (tawazun), tolerance (tasamuh), and justice (i'tidal) are systematically implemented in both credit-based and non-credit curricula, including courses outside the religious field. UIJ has designed teaching methods that encourage students to not only understand these values theoretically but also apply them in daily life, achieved through a student-centered learning (SCL) approach that facilitates dialogue, inquiry, and material exploration by students.